Does the Integrated Health Post have Contextual Effect on Exclusive Breastfeeding? A Multilevel Evidence from Karanganyar, Central Java - ‘Arub, Lathifah; Pamungkasari, Eti Poncorini; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Breastfeeding provides amazing benefits for the health of the child and the mother. WHO and UNICEF suggest a mother should be able to practice and maintain exclusive breast